1) (x-2) (x-3) + (x+6) (x-5) - 2 (x квадрате-7x+13) при x=5,62) (3m-1) (m+1) + (2m-1) (m-1) - (5m+5) (m-2) при m=0.375

+2
Ответы (1)
  1. 13 сентября, 00:34
    0
    Упростим:

    1) (х - 2) * (х - 3) + (х + 6) * (х - 5) - 2 * (х^2 - 7 х + 13) = х^2 - 3 х - 2 х + 6 + х^2 - 5 х + 6 х - 30 - 2 х^2 + 14 х - 26 = 2 х^2 - 2 х^2 - 5 х + х + 14 х - 24 - 26 = 10 х - 50.

    Найдем значение выражения если х = 5,6:

    10 * 5,6 - 50 = 56 - 50 = 6.

    Ответ: 6.

    2) (3m - 1) * (m + 1) + (2m - 1) * (m - 1) - (5m + 5) * (m - 2) = 3m^2 + 3m - m - 1 + 2m^2 - 2m - m + 1 - (5m^2 - 10m + 5m - 10) = 5m^2 - m - 5m^2 + 10m - 5m + 10 = 4m + 10.

    Найдем значение выражения, если х = 0,375:

    4 * 0,375 + 10 = 1,5 + 10 = 11,5.

    Ответ: 11,5.
Знаешь ответ на этот вопрос?